Comparison of 21-Plex PCR and API 20C AUX, MALDI-TOF MS, and rDNA Sequencing for a Wide Range of Clinically Isolated Yeast Species: Improved Identification by Combining 21-Plex PCR and API 20C AUX as an Alternative Strategy for Developing Countries - Arastehfar, Amir; Daneshnia, Farnaz; Kord, Mohammad; Roudbary, Maryam; Zarrinfar, Hossein; Fang, Wenjie; Hashemi, Sayed Jamal; Najafzadeh, Mohammad Javad; Khodavaisy, Sadegh; Pan, Weihua; Liao, Wanqing; Badali, Hamid; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Occurrence of non-Candida albicans Candida (NCAC) species that are associated with elevated MIC values and therapeutic failures are increasing. As a result, timely and accurate means of identification to the species level is becoming an essential part of diagnostic practices in clinical settings. In this study, 301 clinically isolated yeast strains recovered from various anatomical sites [Blood (n=145), other sites (n=156)] were used to assess the accuracy and practicality of API 20C AUX and 21-plex PCR compared to MALDI-TOF MS and large subunit rDNA (LSU rDNA). MALDI-TOF MS correctly identified 98.33% of yeast isolates, 100% of top five Candida species, 95.7% of rare yeast species, while 1.3% of isolates were misidentified. API 20C AUX correctly identified 83.7% of yeast isolates, 97.2% of top five Candida species, 61.8% of rare yeast species, while 16.2% of yeast isolates were misidentified. The 21-plex PCR, accurately identified 87.3% of yeast isolates, 100% of top five Candida species, 72% of rare yeast species, but it misidentified 1.3% of rare yeast species while 9.9% of whole yeast isolates were not identified. The combination of rapidity of 21-plex PCR and comprehensiveness of API 20C AUX, led to correct identification of 92% of included yeast isolates. Due to expensiveness of MALDI-TOF MS and sequencing, this combination strategy could be the most accurate and inexpensive alternative identification strategy for developing countries. Moreover, by the advent and development of cost-effective, reliable, and rapid PCR machines that cost 130 US dollars, 21-plex could be integrated in routine laboratories of developing and resource-limited countries to specifically identify 95% causative agents of yeast-related infections in human. Databases of MALDI-TOF MS, API 20C AUX, and the number of target species identified by 21-plex require further improvement to keep up with the diverse spectrum of yeast species.